STRATEGI PEMASARAN TRAVEL HAJI DAN UMROH PT NUR RAMADHAN WISATA CABANG SURABAYA DALAM MENINGKATKAN DAYA TARIK MASYARAKAT - Muhammad Lutfi Mukhtar; Cucu Hayati; Fatchurrohman, Mochamad (Ekomania, 2023)
In the midst of the Covid-19 pandemic, which is still an epidemic in the world, one of which is in Indonesia, many companies have to rethink their marketing strategies. This research was conducted at PT NUR RAMADHAN WISATA Surabaya Branch. This research was conducted to find out what strategy is used by PT NUR RAMADHAN WISATA Surabaya Branch to increase the attractiveness of the community. This research has two problem formulations, namely What marketing strategy is used by PT NUR RAMADHAN WISATA Surabaya Branch to increase the attractiveness of the community and also what are the factors that support and hinder the marketing strategy of PT NUR RAMADHAN WISATA WISATA Surabaya Branch to increase public attractiveness. This study uses a type of field research using primary and secondary data sources. The data collection techniques used are interviews, observation, and documentation. The data analysis technique used in this research is qualitative descriptive technique. The results of this study indicate that PT NUR RAMADHAN WISATA Surabaya Branch in increasing the attractiveness of the community using the method of going directly to the community through village events such as recitation of fathers or mothers. In addition, PT NUR RAMADHAN WISATA Surabaya Branch also went directly to private and government agencies and also to schools. Next is to use social media and always prioritize service. Next is to re-establish the company order. The supporting factors for the marketing strategy of PT NUR RAMADHAN WISATA Surabaya Branch to increase the attractiveness of the community include: Having complete offices and facilities, having SOPs for all employees, conducting routine trainings for employees, having an experienced marketing team, holding regular monthly meetings with the head office, and finally having products that suit the needs of the community. . While the inhibiting factor is the number of companies engaged in the same field, namely Hajj and Umrah travel midwives